Injuries in male youth football: a one season prospective cohort study of 223 Danish elite players - Andersen, T. R.; Drevsfeldt, A.; Möller, S.; Møller, M. (Frontiers in Sports and Active Living, 2023)
Objectives This study prospectively investigated injury prevalence, incidence, and burden in male elite under-17 football players (N = 223) during a full season.